Mortgage Loan – A Key Factor on the Market of Residential Real Estates - Stefanov, Dragomir (Research Papers, 2018)
The residential real estate market is one of the most dynamically developing and significant market for any society. The main topic of the present study is to analyze the factors that have the main impact over this market and, in particular, mortgage lending. For this purpose, subject for examinations are the interest rates and the volumes of household loans granted in Bulgaria in the period 2007 – 2018.The made conclusions in the study confirm the author’s thesis that mortgage lending is a key factor in the property market and can serve in favor to forecasting market trends to potential investors and entrepreneurs.